Improved electron extraction by a ZnO nanoparticle interlayer for solution-processed polymer solar cells. Issue 20 (21st February 2017) - Zhang, Xuning; Yang, Shuo; Bi, Shiqing; Kumaresan, Anbu; Zhou, Jiyu; Seifter, Jason; Mi, Hongyu; Xu, Yun; Zhang, Yuan; Zhou, Huiqiong
Abstract : Solvent effect on hole-blocking layers based on ZnO nanoparticles is investigated for solution-processed polymer solar cells. Incorporation of the dense ZnO nanoparticle interlayer leads to enhanced PCEs in PTB7-Th:PC71 BM solar cells from 8.4% to 9.2% with improved stability. Abstract : Charge injection/extraction properties dictate the device characteristics of polymer solar cells. Based on a model system comprising PTB7-Th:PC71 BM blends, we investigate solvent effects and interface properties of ZnO nanoparticles used as electron-transporting/hole blocking interlayers (ETL/HBL) to improve the solar cell performance and stability. We find that the polarity of processing solvents and thickness of ZnO nanoparticles ETL both play a crucial role in the device behavior. Under the optimal conditions, the power conversion efficiency (PCE) is increased from 8.4% to 9.2% for PTB7-Th:PC71 BM solar cells with a conventional device architecture, which is among the highest efficiencies for this blend system. The simultaneous increase in short-circuit current ( J sc ) and fill factor (FF) originates from an effective hole blocking mechanism provided by the ZnO layers which increase the selectivity of charge extraction and reduce non-geminate charge recombination. The dense and air-stable ZnO ETLs minimize the diffusion of moisture and O2 into the photoactive layer, leading to drastically improved device stability.